Respuesta :
Answer:
Step-by-step explanation:
(6x-3)=(4x+33)
Combine like terms,
Subtract 4x on both sides and add 3 to both sides
2x=36
Divide by 2 on both sides
X=18
In order to solve for x, we can do the following:
6x - 3 = 4x + 33
6x - 3 + 3 = 4x + 33 + 3 (Add 3 to both sides)
6x = 4x + 36 (-3 + 3 = 0; 33 + 3 = 36)
6x - 4x = 4x + 36 - 4x (Subtract 4x from both sides)
2x = 36 (6x - 4x = 2x; 4x - 4x = 0)
2x/2 = 36/2 (Divide both sides by 2)
x = 18 (2x/2 = x; 36/2 = 18)
Thus, the value of x is 18.